STUDI PENILAIAN EKONOMIS PERENCANAAN SISTEM INSTALASI BIOGAS PADA KAPAL KARGO (KM.SINAR BUGIS) DENGAN METODE (COST & BENEFIT ANALYSIS) - Samsudin (Fakultas Sains dan Teknologi Universitas Karimun, 2021)
The biogas installation system is planned to be installed on the Kago KM ship. Sinar Bugis in terms of advantages and disadvantages in a system of cost and benefit systems. This system is planned to contribute energy supply for electricity utilization on ships and for gas cooking. The biogas installation planning scheme is made by considering the variable number of passengers and the fermentation period to be carried out. With the ability to produce gas in the range of 13 m3 per day, with the conversion of electric energy of 5.4 Kwh / m3, with 1900 passengers it is estimated that they can generate new energy of 65.3 Kwh and be able to provide cooking energy for 87 people. Meanwhile, the cost identification shows that the procurement cost is IDR 4,000,000. Start-up cost is IDR 98,750,000 and the ongoing cost is IDR 83,000,000. The total benefit value assuming the current energy price variable is IDR 162,998,620.- so that the cost and benefit identification value is obtained a BCR value of 3.17